TRANSPARENCY OR SECRECY? BUSINESS-GOVERNMENT RELATIONS IN A NETWORKED ERA - Roy, Jeffrey (The journal of contemporary issues in business and government, 2007)
This article examines how the patterns of business-government relations are changing in an increasingly networked era. The primary focus in this investigation is the widening scope of collaboration and partnerships between both sectors, and the arguments for and against such interaction. Subsequently, how these arguments relate to transparency and secrecy in the formation of new governance arrangements as well as accountability and performance of such arrangements are also considered. The essential role of transparency is put forth as the key to being able to distinguish between collaboration and collusion and to promote the former as a basis of more virtuous hybrid governance models enjoining business and government.